Diet affects gut microbiota and modulates hospitalization risk differentially in an international cirrhosis cohort. Issue 1 (10th May 2018) - Bajaj, Jasmohan S.; Idilman, Ramazan; Mabudian, Leila; Hood, Matthew; Fagan, Andrew; Turan, Dilara; White, Melanie B.; Karakaya, Fatih; Wang, Jessica; Atalay, Rengül; Hylemon, Phillip B.; Gavis, Edith A.; et al.
Abstract : The relative ranking of cirrhosis‐related deaths differs between high‐/middle‐income countries. Gut microbiome is affected in cirrhosis and is related to diet. Our aim was to determine the effect of differing dietary habits on gut microbiota and clinical outcomes. Outpatient compensated/decompensated patients with cirrhosis and controls from Turkey and the United States underwent dietary and stool microbiota analysis. Patients with cirrhosis were followed till 90‐day hospitalizations. Shannon diversity and multivariable determinants (Cox and binary logistic) of microbial diversity and hospitalizations were studied within/between groups. Two hundred ninety‐six subjects (157 U.S.: 48 controls, 59 compensated, 50 decompensated; 139 Turkey: 46 controls, 50 compensated, 43 decompensated) were included. Patients with cirrhosis between cohorts had similar Model for End‐Stage Liver Disease (MELD) scores. American patients with cirrhosis had more men, greater rifaximin/lactulose use, and higher hepatitis C/alcohol etiologies. Coffee intake was higher in Americans whereas tea, fermented milk, and chocolate intake were higher in Turkey. The entire Turkish cohort had a significantly higher microbial diversity than Americans, which did not change between their controls and patients with cirrhosis. In contrast, microbial diversity changed in the U.S.‐based cohort and was the lowest in decompensated patients. Coffee, tea, vegetable, chocolate, and fermented milk intake predicted a higher diversity whereas MELD score, lactulose use, and carbonated beverage use predicted a lower microbial diversity. The Turkish cohort had a lower risk of 90‐day hospitalizations. On Cox and binary logistic regression, microbial diversity was protective against 90‐day hospitalizations, along with coffee/tea, vegetable, and cereal intake. Conclusion : In this study of patients with cirrhosis and healthy controls from the United States and Turkey, a diet rich in fermented milk, vegetables, cereals, coffee, and tea is associated with a higher microbial diversity. Microbial diversity was associated with an independently lower risk of 90‐day hospitalizations. (Hepatology 2018;68:234‐247).